Perkawinan Beda Agama dan Implikasinya Terhadap Terbitnya Kartu Keluarga Perspektif Undang-undang No. 1 Tahun 1974 dan Undang-undang No. 23 Tahun 2006 : (Studi Kasus Kecamatan Naman Teran, Kabupaten Karo) - Wike Sundari; Amal Hayati (UNES Law Review, 2024)
Marriage is a spiritual and physical relationship between a man and a woman as husband and wife, with the goal of creating a happy family based on the belief in the Almighty God. One of the marriages that often occurs in Indonesia is marriage between different religions. Law Number 1 of 1974 outlaws interfaith marriages, as stated in article 2 paragraph 1: "marriage is valid if carried out according to the laws of each religion and belief." Meanwhile, Law Number 23 of 2006 allows for interfaith marriages, as indicated in Article 35, which specifies that marriages determined by the court are 'interfaith marriages'. This research method is qualitative, it utilizes normative empirical legal research, a comparative perspective, and legal sociology, and the data is gathered from books, journals, articles and interviews. According to the author, the more relevant law is the regulation of Law Number I of 1974 which prohibits interfaith marriages. Because it allows couples to manage the legality of their marriage without having to use illegal method in order to fulfill administrative rights such as issuing Family Cards and other administrative procedures.